The aMAZEing Brain - Saad, Wan Zuhainis; Sabri, Suriana; Shakeeb Arsalaan Bajunid, Siti Farhana Bajunid (Universiti Putra Malaysia Press, 2016)
Trillions of neural network are connected to one another in the brain. “The aMAZEing Brain” is the product of the thoughts generated in a whimsical way by these connections. This model appears to be a brain figure with many partitions representing different brain regions.